Analisis Pengaruh Rasio Keuangan, Pertumbuhan Penjualan, Deviden, Dan Economic Value Added Terhadap Harga Saham Di Perusahaan Manufaktur (Studi Empiris di Bursa Efek Indonesia Tahun 2011-2014) - Putri, Rahmawati; , Dr. Fatchan Ahyani, SE., M. (2016)
The purpose of this study to analyze the liquidity, profitability, sales growth, dividends, and economic value added to the stock price. The share price is a feflection of the conditition of a company where the stock prices in the stock price will return for investors in the form of capital gains which ultimately will affect the company's image. The population used in this study are all manufacturing companies listed on the stock exchange indonesian. The sampling method wih a purposive sampling in accordance with the criteria specified. The number of samples collected as many as 12 companies with 48 data, with the data the outliers as much as 3 to 45 samples of data. The collected data were analyzed using data analysis conducted prior classic assumption test before hypothesis test. Testing the hypothesis in this study using multiple regression analysis. Based on the research that has been done, it is known liquidity, profitability, sales growth, and dividens effect on stock prices, while the economic value added has no effect on stock prices.